Assessment of factors enabling halite formation in a marsh in a humid temperate climate (Ajó marsh, Argentina) - Carol, Eleonora Silvina (2016)
The formation of evaporites associated with the final stages of the precipitation sequence, such as the case of halite, is frequent in marshes in arid areas, but it is not to be expected in those humid climates. This work, by means of the study of the hydrological, climatic and land use conditions, identifies the factors that allow the formation of saline precipitations in a marsh located in a humid climate area. The results obtained show that the exclusion of the marsh as a result of the embankment is the main reason for the presence of halite. It is to be expected that in the future the growth of the embanked marsh areas, together with the climatic and tidal condition tendencies recorded, will favour a higher rate of formation of evaporite salts. The identification of these factors makes it possible to set basic sustainable management guidelines to avoid soil salinisation.